Effect of seed different levels of NPK fertilizers and irrigation on yield and nutritive quality of mulberry leaf (Bangladesh Journal of Agricultural Research, 2009)
Experiment was conducted at the research field of Bangladesh Sericulture Research and Training Institute, Rajshahi in 2001-2002 and 2002-2003 to investigate the effect of NPK fertilizers and frequency of irrigation on leaf yield, yield components and leaf quality characters of three mulberry varieties. Four levels of NPK fertilizers and three levels of irrigation were adopted. The treatments comprising 300 kg N, 150 kg P, and 100 kg K/ha/yr along with two irrigations in a month was found to be the best for higher leaf yield, leaf moisture and leaf nutrient contents of mulberry plants (var. BM-3). Key Words: Mulberry, NPK fertilizers, irrigation, nutritive quality. DOI: 10.3329/bjar.v34i3.3969 Bangladesh J. Agril. Res. 34(3) : 435-442, September 2009